De Novo MYC and BCL2 Double-hit B-Cell Precursor Acute Lymphoblastic Leukemia (BCP-ALL) in Pediatric and Young Adult Patients Associated With Poor Prognosis. (17th November 2015) - Liu, Wei; Hu, Shimin; Konopleva, Marina; Khoury, Joseph D.; Kalhor, Neda; Tang, Guilin; Bueso-Ramos, Carlos E; Jorgensen, Jeffrey L.; Lin, Pei; Medeiros, L. Jeffrey; Lu, Xinyan
Abstract : MYC and BCL2 translocations in B-cell lymphomas are defined as "double-hit" associated with poor prognosis in adult patients. Such double-hit events are extremely rare in B-cell precursor acute lymphoblastic leukemia (BCP-ALL), especially in pediatric patients or young adults. This study is to investigate the clinical manifestation of de novo MYCyBCL2 double-hit BCP-ALL in young patients. Two pediatric and one young adult patients were identified after a retrospective data review and all without previous history of lymphoma. There were two females and one male aged 15, 18, and 24, respectively. All patients had an unremarkable medical history before presenting with extensive bone marrow and central nervous system involvement at diagnosis. Flow cytometry immunophenotypic analysis showed an immature B-cell immunophenotype (CD10+, CD19+, TdT+, surface Ig-) and immunohistochemistry showed high expression of MYC and BCL2 in all cases. All patients showed complex karyotypes associated with 8q24 abnormalities in the form of t(8;9)(q24;p13) or t(8;14)(q24;q32) and t(14;18)(q32;q21) and fluorescence in situ hybridization confirmed MYC and BCL2 rearrangements. Two patients died of refractory disease or disease progression 7 and 13 months after initial diagnosis, respectively, and the third patient was treated with protocol AALL0232 under the Children's Oncology Group study, achieved complete remission and remained in remission for 53 months at last follow-up. Our study showed that De novo MYCyBCL2 double-hit BCP-ALL is a rare disease that also occurs in pediatric and young adult patients and associated with complex karyotypes and poor prognosis. Younger patients may benefit from intensified chemotherapy.